Evaluation of Egg Quality Indices, Fertility, Hatchability % and Some Biochemical Parameters under the Effect of Some Environmental Stressors in Laying Hen - Ghanem , H.M.; Manaa, E.A.; Saleh, R.M. (International Journal of Poultry Science, 2017)
Objective: The aim of the present study was to investigate the effect of some environmental stressors (temperature and humidity) on egg quality indices, fertility and hatchability % and some biochemical data in laying hen. Materials and Methods: One hundred and eighty adult laying hens at 20 weeks of age were selected and used in this current experiment. The birds were randomly divided into three groups of 60 each and each group was further divided into five replicates of 12 birds. Three stages of thermal comfort values were established such as: Normal <74, alert from 75-78, danger values are those from 79-83. Results: Control group (which housed at normal THI <74) achieved the highest significant egg quality traits, egg efficiency indices, comparing to thermally stressed groups. Exposure of birds to high THI (T2) causes a significantly (p<0.01) decrease in the fertility and hatchability %. It was noticed that thermal stress could significantly (p<0.01) affect serum levels of T3 to reach the peak value in the stressed group. On the reverse directions, the serum level of T4 achieved the highest significant level in the control group and the lowest value was achieved in thermally stressed groups. On the same way, the level of plasma proteins or lipid profile showed a highly significant (p<0.001) increase in control group than groups exposed to thermal stress. Corticosterone level achieved the high level in thermally stressed groups. In addition, TLC showed the highest significant level in the stressed group compared to the low level in the control group. Conclusion: Laying hen exposed to high environmental conditions revealed decline in egg quality and production, fertility, hatchability and some biochemical parameters. Therefore, the birds should house in good environmental conditions in order to maintain the production and consequently the economic income.